2013
DOI: 10.4049/jimmunol.1201195
|View full text |Cite
|
Sign up to set email alerts
|

Self Double-Stranded (ds)DNA Induces IL-1β Production from Human Monocytes by Activating NLRP3 Inflammasome in the Presence of Anti–dsDNA Antibodies

Abstract: The pathogenic hallmark of systemic lupus erythematosus (SLE or lupus) is the autoimmune response against self nuclear antigens, including dsDNA. The increased expression of the pro-inflammatory cytokine IL-1β has been found in the cutaneous lesion and peripheral blood mononuclear cells from lupus patients, suggesting a potential involvement of this cytokine in the pathogenesis of lupus. IL-1β is produced primarily by innate immune cells like monocytes and can promote Th17 cell response, which is increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 52 publications
5
94
1
2
Order By: Relevance
“…Quantitative reverse transcriptase polymerase chain reaction and GATA3 gene knockdown were done as previously described with some modifications (see the online supplement METHODS) (22).…”
Section: Microarray and Gene Knockdownmentioning
confidence: 99%
“…Quantitative reverse transcriptase polymerase chain reaction and GATA3 gene knockdown were done as previously described with some modifications (see the online supplement METHODS) (22).…”
Section: Microarray and Gene Knockdownmentioning
confidence: 99%
“…Ultimate assembly and activation of the inflammasome requires ligands specific for different inflammasome scaffolds or cellular metabolic changes. These “signal 2” stimuli are as diverse as bacterial peptidoglycans, crystalline materials, oxidative stress and nucleic acids (1013). …”
Section: The Inflammasomementioning
confidence: 99%
“…Caspase-1 is inhibited by thalidomide, a medication used for multiple myeloma and for refractory rheumatic disease such as cutaneous lupus(21, 22). Antimalarial medications, such as hydroxychloroquine and chloroquine, which interferes with toll-like receptor (TLR) 7 and 9 activation in the lysosomal compartment, blocks inflammasome activation and IL-1β release following certain inflammasome activating triggers(13, 23). Colchicine, which inhibits microtubule assembly, is able to block inflammasome activation by preventing co-localization of ASC with NLRP3(24, 25).…”
Section: Targeting Inflammasome Activation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Kahlenberg, et al demonstrated an upregulation of NLRP3 and caspase-1 in lupus nephritis biopsies [8]. Furthermore, immune complexes such as complement and autoantigen/autoantibody complex have been demonstrated to induce inflammasome activation through the stimulation of TLR dependent activation of NFκB, which then causes the NLRP3 inflammasome activation [9,10]. Neutrophil extracellular traps have been recently demonstrated, and could activate caspase-1, causing IL-1β and IL-18 over expression in macrophages derived from SLE patients [11].…”
Section: Introductionmentioning
confidence: 99%